Condom Use Behavior among Female Sex Worker Clients in Makassar City - Jariyah, Ainun; Leli, Leli; Saad, Rahmiyani; Rosdiana, Rosdiana; Mahendika, Devin; Anurogo, Dito (International Journal of Health Sciences, 2024)
Indonesia has not yet emerged as one of the countries with the highest HIV/AIDS epidemic rate in the world. The United Nations Organization for AIDS, namely the United Nations Joint Program on HIV and AIDS, said that over the past two years, Indonesia's position has not changed, namely that it is still the country with the fastest AIDS epidemic in Asia. HIV-AIDS transmission in Indonesia is growing rapidly, one of the triggers is risky sexual behavior, including sexual behavior among female sex worker clients. This study aims to analyze the factors that influence condom use behavior among female sex worker clients in Makaassar. This research uses quantitative methods with an explanatory research design with a cross sectional approach. Qualitative data carried out as triangulation was used to support the results of quantitative analysis extracted from female sex workers and pimps as a cross check of answers from female sex worker customers. The method used was in-depth interviews and Focus Group Discussions on female sex workers and pimps. The sample size was 66 people. Data analysis was univariate, bivariate with chi-square and multivariate with logistic regression. The results show that the majority of respondents (71.2 %) behave consistently in using condoms.